DETERMINAN STRUKTUR MODAL PERBANKAN SYARIAH ASIA DAN EROPA - Rifqi Muhammad; Risca Azmiana (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
Capital structure is an important component in building a strong business entity. The banking industry is a commercial entity that requires a strong capital structure management to ensure its business continuity. Moreover, the Islamic banking business model prioritizes the strength of the equity structure over debt. Islamic banking manages temporary syirkah funds as a form of investment for customers with the hope of obtaining optimal profit sharing. Therefore, this study examines the factors that have the potential to influence the capital structure of the Islamic banking industry. These factors include: company size, profitability, growth, and asset structure. This study used a purposive sampling technique using 24 samples of Islamic banks in Asia and Europe with certain criterias. This study conducted tests with panel data analysis and statistical applications to measure the influence of factors affecting the capital structure of Islamic banks in Asia and Europe. Finally, this study finds that asset structure has no effect on capital structure and profitability has a positive effect on capital structure. Meanwhile, firm size and growth variables have a negative effect on capital structure.